2021
DOI: 10.1016/j.ultsonch.2021.105607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic pre-treatment on Ara h 1 in peanut sprouts

Abstract: Highlights US pre-treatment had profound effects on Ara h 1 protein in peanut sprouts. Protease activity increased significantly during germination after US. Cavitation and the heat effect from US destroyed intramolecular hydrogen bonds and resulted in the blue shift phenomenon. The gene expression level of Ara h 1 was significantly lower in the US group than in the control BK group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Ara h 1 is an allergen of 7S globulin belonging to the vicilin protein family with a molecular weight of around 65 kDa 24,32 and accounted for about 12% of peanut general protein. 33,34 For the preparation of Ara h 1, IEC was performed, and Ara h 1 protein with increased purity was obtained to ensure the successful screening of positive Nbs that specifically recognize Ara h 1 by comparing with application of unbiased strategies using crude protein extracts instead of the completely pure allergen. It is always difficult to purify allergen from crude protein extract, and thus, the purification steps to help increase the purity are preferred if the allergen of interest has been thoroughly characterized.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ara h 1 is an allergen of 7S globulin belonging to the vicilin protein family with a molecular weight of around 65 kDa 24,32 and accounted for about 12% of peanut general protein. 33,34 For the preparation of Ara h 1, IEC was performed, and Ara h 1 protein with increased purity was obtained to ensure the successful screening of positive Nbs that specifically recognize Ara h 1 by comparing with application of unbiased strategies using crude protein extracts instead of the completely pure allergen. It is always difficult to purify allergen from crude protein extract, and thus, the purification steps to help increase the purity are preferred if the allergen of interest has been thoroughly characterized.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This study reported for the first time the successful selection of specific Nbs against peanut allergen of Ara h 1 and the development of Nb-pair based immunoassays. Ara h 1 is an allergen of 7S globulin belonging to the vicilin protein family with a molecular weight of around 65 kDa , and accounted for about 12% of peanut general protein. , For the preparation of Ara h 1, IEC was performed, and Ara h 1 protein with increased purity was obtained to ensure the successful screening of positive Nbs that specifically recognize Ara h 1 by comparing with application of unbiased strategies using crude protein extracts instead of the completely pure allergen. It is always difficult to purify allergen from crude protein extract, and thus, the purification steps to help increase the purity are preferred if the allergen of interest has been thoroughly characterized. ,, The binding specificity of obtained Nbs to the target antigen of Ara h 1 has been further verified by ELISA, and the target antigen was investigated by performing immunocapturing and LC–MS/MS to completely understand the binding of these Nbs to the peanut allergen of Ara h 1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the germination progressed, the content of allergen Ara h 1 was greatly reduced . The reduction in the allergen contents induced by ultrasonic pretreatment was recently analyzed, attributed to the inhibitory effects of US treatment on the expression of Ara h 1 gene and the structural disruption of the gene product, which were characterized by the decreased α-helix structure, the increased β-fold structures and the loose tertiary structures of Ara h 1 after US treatment …”
Section: Gaba Concentration Variability Responding To Nonthermal Stre...mentioning
confidence: 99%
“…Using ultrasound treated Pinus tabuliformis seeds has been adopted in large scale aircraft sowing based afforestation in North China over 30 years’ ago, especially in short rainy season which requires fast germination in harsh conditions [16] . Studies showed ultrasound treatment promoted seed germination in diverse plant species including tall fescue [17] , peanut [18] and rice [19] , in which several germination-related enzymes including α-amylase increased their activities after ultrasoundation. Interestingly, another similar treatment, laser, can increase germination of Chinese pine seeds especially under drought condition, which is correlated with reduced malondialdehyde, a common product of lipid peroxidation [20] .…”
Section: Introductionmentioning
confidence: 99%